NEW PHARMACEUTICALS. HOW CAN INNOVATIVENESS? - V.V. Omel'yanovskii; M.V. Sura; N.D. Sveshnikova (Педиатрическая фармакология)
The article describes the basic approaches to evaluating innovativeness of pharmaceuticals, Russian and foreign experience is represented. The authors pay particular attention to the state involvement in the promotion of new products and create regulatory systems for quality control. The issues of creating a unified system of evaluation of pharmaceuticals innovativeness, which is associated with the need to develop a total innovativeness of pharmaceuticals «scale».Key words: innovations, innovativeness, therapeutic innovativeness.